(untitled) (SCIENCE TIME JOURNAL, 2023)
The given article deals with the stylistic device simile in Karakalpak poetic and text discourse. Stylistic device can be found where an author tries to stress some idea or to make an impression on his readers by using language, that is in some way extraordinary. Stylistic devices are distinguished by creating a certain image. To use a simile is to characterize one object by bringing it into contact with another object belonging to an entirely different class of things.